(untitled) (ModaPalavra e-periódico, 2015)
There isa large number of people with some degree of visual impairment in Brazil, which have difficulties in common tasks of everyday life, such as dressing and choosing a piece of cloth. This paper aims to discuss the inclusive aspects applicable to fashion design for visually impaired people, seeking to support a proposal of clothing that includes self-esteem, practicality, comfort and autonomy of users without, however, differentiate them from general consumers. The proposals are based on surface design -through the application of details in relief and Braille -inclusive fashion and universal design.